Analysis Of Work Motivation and Work Discipline on Employee Performance at the Manyaran Subdistrict Office - Lilis Prasetianingsih; Zandra Dwanita Widodo; Atik Lusia (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study aims to examine the factors that motivate employees to work and how their work discipline relates to their work performance at the Manyaran Subdistrict Office, Wonogiri Regency. This study uses a qualitative descriptive approach, with data collection through interviews, direct observation, and document collection from employees. The data were then analyzed thematically using NVivo 14 software to find patterns and relationships between concepts. The results show that employee work motivation is influenced by how they perceive their work as a responsibility and a form of service, leadership style, the existence of rewards, a comfortable work environment, and the availability of adequate facilities. Work discipline is evident in adherence to rules and work schedules, supervisory actions, and the application of sanctions as a form of supervision and training. The findings indicate that work motivation and work discipline complement each other in shaping employee performance. Good performance is demonstrated by good teamwork, timeliness, quality of work, and improved public services. Therefore, consistently improving work motivation and strengthening work discipline are important factors in improving employee performance in the sub-district government environment.